Speaking of Freedom: U.S. Multicultural Literature and Human Rights Talk In an Emerging Democracy - Levin, Amy (Radical Teacher, 2015)
It’s 100 degrees in Yangon (formerly Rangoon), and I am trying to explain to a student that when she analyzes irony in Hamlet in her MA thesis, she may want to consider politics and the ways in which Shakespeare commented both on Elizabethan England and the nature of power more generally. Ophelia doesn’t even come up in the conversation. I pause for a moment to adjust the feeble fan near my desk, imagining a Danish winter. The potential parallels between the play and the political situation in my host country are glaringly obvious. Dare I say something? Is my student oblivious to this matter, or is she choosing to ignore it, knowing the fragility of human rights in the emerging democracy? In February 2013, I served as the first US Fulbright scholar in a Myanmar public university in almost thirty years. Our discipline was chosen for this venture because, according to the project overview, “American literature is not a sensitive subject with the Ministry of Education and thus a good idea.” Knowing it to be risky, I introduced Masters students and their faculty to recent US literature, focusing primarily on works by women and minorities beginning with the Civil Rights movement. My texts were selected from those I teach in my course on US women writers at home, but in Myanmar, they were discussed with predominantly female groups representing the many religious and ethnic groups within Myanmar. On other occasions, I met with women from NGOs or participated in programs on Women’s Studies and issues such as human trafficking. The experience yielded multiple opportunities to reflect and theorize about the nature of global rights and reciprocity; I was able to compare how women in Myanmar and the US responded to concerns relevant to marginalized populations, even as I confronted issues arising from post-colonialism and male privilege daily. Yet the most intriguing parts of the experience were the silences, evasions, and hesitations which constantly interrupted conversations about the opportunities for improving civil rights in the shift toward democracy. Slowly, we were able to use literature to draw implicit parallels and open conversations about “sensitive topics” so that in the end, the experience was transformative for all of us. Adapting a line from a Naomi Shihab Nye poem, one of my students wrote, “Until you speak Myanmar, you will not understand freedom.” And she was right. My presentation will analyze how US multicultural women’s literature provided scaffolding for more extensive conversations about women and human rights, drawing on literary theory and student narratives as appropriate.